Design of interactive whiteboard system for collaborative learning - Madni, T.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
The research in the education system describes that the students generally do not produce good results because of the use of traditional ways of educational system. It has been identified that the use of interactive technologies, constructive methods and appropriate interfaces has a great impact in improving creative education and learning. With the advancements of Interactive technologies provides initiative human-computer interaction as compared with conventional mouse and keyboards. A prototype of interactive whiteboard was developed to analyze the effectiveness of students learning system which enables co-location, multiple users, hands-on activities and multiple-modes of communication using hand-held laser pointer device(s). This collaborative learning prototype enables the use of laser pointer(s) to interact with the whiteboard. The laser pointer controls mouse events and additional gesture events as with same functionality provided by conventional mouse pointer. Furthermore, a quantitative investigation on the usefulness of collaborative learning system was conducted with twenty participants. The participants showed deeper and more interactive learning experience. The results of study show, substantial use of this technology in classrooms and meeting rooms which can improve the effectiveness of brainstorming sessions. Â© 2014 IEEE.